PENGEMBANGAN KURIKULUM 2013: PEMBELAJARAN BAHASA ARAB DI MADRASAH ALIYAH - Arif, Muh; Makalalag, Chendra (STAI Darul Qalam Tangerang, 2022)
One of the problems of education in Indonesia is that the curriculum has never been established, even though it has changed the curriculum too much. This research discusses the development of the 2013 curriculum in Madrasah Aliyah with a focus on analyzing the substance of the latest curriculum, namely KMA No. 183 and 184 of 2019 in Arabic subjects. The method used is descriptive qualitative with a content analysis model. The results of this study contribute in the form of understanding and opening the horizons of thinking of teachers that this new curriculum is no longer a rigid curriculum, therefore teachers as curriculum users must be innovative and flexible